Copper Catalyzed Direct Synthesis of Nitriles from Acyl Azides. Issue 43 (23rd November 2018) - Chen, Yang; Liu, Yu; Zhang, Xiao; Lu, Da; Yang, Lixin; Deng, Junfeng; Deng, Shengqi
Abstract: A novel and general protocol for the copper catalyzed reductive elimination of acyl azides to nitriles using triethoxysilane is reported. Various nitriles are obtained in moderate to excellent yields with good functional group tolerance and high chemoselectivity under mild conditions. This new reaction can be performed using a cheap copper catalyst, a simple NHC ligand, an inexpensive silane, and with low catalyst loading. Abstract : A novel and general protocol for the copper catalyzed reductive elimination of acyl azides to nitriles using triethoxysilane is reported. Various nitriles are obtained in moderate to excellent yields with good functional group tolerance and high chemoselectivity.